Parameters for dimensional inspection of orifice plates and roughness of the straight stretches of the tubing - Medeiros,Alberto Kennedy de Almeida (2006)
According to the Technical Regulation of Measurement of Petroleum and Natural Gas (approved in 2000 by ANP - the Petroleum National Agency of Brazil), the systems of measurement of natural gas should use ultra-sonic flow meters, turbines and, especially, the orifice plates, which represent the most expressive base of the flow systems, being used in the fiscal and operational measurements. This work aims to evaluate the parameters that should be accounted for during the dimensional inspection of orifice plate and roughness of the straight stretches of the tubing used for measurement of natural gas, with the objective of guiding the responsible professionals for the measurement of volumes of natural gas by orifice plate, as well as the professionals of calibration laboratories. In this work, minimum specifications are recommended, irrespective of the pressure tapping or orifice type, in agreement with the norms ISO, AGA and the ANP regulations. The influence of these specifications on the parameters used in the calculation of the volumetric flow is also analyzed.